Data Mountain: Using Spatial Memory for Document Management - Robertson, George; Czerwinski, Mary; Larson, Kevin; Robbins, Daniel; Thiel, David; Dantzich, Maarten van (UIST '98: Proceedings of the 11th annual ACM symposium on User interface software and technology, 1998)
Effective management of documents on computers has been a central user interface problem for many years. One common approach involves using 2D spatial layouts of icons representing the documents, particularly for information workspace tasks. This approach takes advantage of human 2D spatial cognition. More recently, several 3D spatial layouts have engaged 3D spatial cognition capabilities. Some have attempted to use spatial memory in 3D virtual environments. However, there has been no proof to date that spatial memory works the same way in 3D virtual environments as it does in the real world. We describe a new technique for document management called the Data Mountain, which allows users to place documents at arbitrary positions on an inclined plane in a 3D desktop virtual environment using a simple 2D interaction technique. We discuss how the design evolved in response to user feedback. We also describe a user study that demonstrates that the Data Mountain does take advantage of spatial memory. Our study demonstrates that the Data Mountain has statistically reliable advantages over the Microsoft Internet Explorer Favorites mechanism for managing documents of interest in an information workspace.